DESAIN LEMARI ARSIPDI PT. BANK RAKYAT INDONESIA (BRI) PERSERO Tbk CABANG GOMBONGMENGGUNAKAN METODE QUALITY FUNCTIONDEPLOYMENT (QFD) - Akhmad Fauzy Nur Hidayako; Ida Betanursanti (Universitas Ahmad Dahlan Indonesia, 2017)
Filling cabinet designs are generally less attention to the aspects that will pose complaints. Thecabinet must has a superiority to diminish indication musculoskeletal disorder, quality, display, andcapacity for collection. The user want the filling cabinet product that safety, easily to use, comfortable.The purpose of research is designing cabinets and organized to the user’s posture.Anthropometry data offilling cabinet taken fromemployees of BRI Gombong branch. After get the data, the researcher willprocess it use statistic test. Filling cabinet organize depend on employ needed with QFD method byengaging in designing to customer wishes to translate the matrix House of Quality (HOQ). Filling cabinetdesigned results in a safety, easy to use and comfortable is was of made wood, with oval shaped edges(not sharp). In the searching of archives, the users are recommended in standing with elbow heightposition about 122-123 cm. The filing cabinet added two ladders and moves them with hydraulic systemto adjusting the height. It has 3 shelves, with grey color. There are 9 boxes, with each box has two shelvesto receive more file. There are index label search on each box for easy search and organizing file.